Layered Double Hydroxide-Based Nanocarriers for Drug Delivery - Xue Bi; Hui Zhang; Liguang Dou (Pharmaceutics, 2014)
Biocompatible clay materials have attracted particular attention as the efficient drug delivery systems (DDS). In this article, we review developments in the use of layered double hydroxides (LDHs) for controlled drug release and delivery. We show how advances in the ability to synthesize intercalated structures have a significant influence on the development of new applications of these materials. We also show how modification and/or functionalization can lead to new biotechnological and biomedical applications. This review highlights the most recent progresses in research on LDH-based controlled drug delivery systems, focusing mainly on: (i) DDS with cardiovascular drugs as guests; (ii) DDS with anti-inflammatory drugs as guests; and (iii) DDS with anti-cancer drugs as guests. Finally, future prospects for LDH-based drug carriers are also discussed.